Evolution of domestic dwellings in Cyprus and energy analysis - Florides, Georgios A.; Wrobel, L. C.; Kalogirou, Soteris A.; Florides, Georgios A.; Tassou, Savvas A.; Wrobel, L. C. (My University, 2001)
This study describes the evolution of domestic dwellings in Cyprus during the twentieth century with respect to their heating and cooling requirements. The methods of construction employed and materials used are also presented. TRNSYS is used for modelling and simulation of the energy flows of various types of houses. For the calculations, a typical meteorological year for the Nicosia area and a typical model plan of a house are used. The inside house temperature, for the various construction methods, when no air-conditioning is used, is estimated. The temperature inside the traditional house varies in a similar manner with a well-insulated modern house. This variation is 16–20°C for winter and between 25–35°C for summer compared to 11–20°C for winter and 33–46°C for summer for a non-insulated house with a flat roof. The summer temperatures drop considerably, by about 5°C, when ventilation air is used for cooling, depending on the number of air changes.
Keywords: Domestic dwellings; TRNSYS